Social capital and the generation of technological innovations in Ecuadorian companies - Morales-Urrutia, Diana (2021)
The objective of this research is to analyze social capital in the generation of technological innovations in Ecuadorian companies. From the methodological point of view, the data from the Ecuadorian Institute of Statistics and Census (INEC) are taken from the ACTI 2012-2014 survey. The results point to the existence of an influence of social capital in the creation of technological innovations in companies. In conclusion, the importance of the networks and the links that are managed strategically in the sectors are highlighted.